Sintesis dan karakteristik nanopartikel CaO dari cangkang kerang darah (Anadara granosa) menggunakan metode kopresipitasi - Nur Hayati; Widodo Budi Kurniawan; Indah Puspita (Jurusan Fisika, Universitas Bangka Belitung, 2024)
The lithium ion battery is a type of secondary battery. A good component to be used as the anode of a lithium ion battery is Li4Ti5O12 (LTO). LTO has a low conductivity value so doping is necessary. Doping particle size greatly affects the conductivity of LTO. The purpose of this doping was carried out to find out how the effect of CaO nanoparticle doping on the conductivity value of the LTO battery anode using the coprecipitation method by varying the molarity of NaOH, namely 1M, 3M and 7M. Based on the results of research on the influence of NaOH molarity, it produces different sizes of nanoparticles. The smallest nanoparticle size was obtained in the 3M sample variation, which was 175.0 nm. With a purity of CaO nanoparticles of 96.35%. While the conductivity value of the lithium ion battery doped with CaO nanoparticles with three variations of NaOH molarity, the optimum value was obtained in the 1M sample, which was 1.06 × 10-6 S/cm. This is because the 1M variation produces very low impurities compared to the 3M and 7M variations which have more impurities, this can affect the conductivity value.